2014
DOI: 10.7314/apjcp.2014.15.12.5019
|View full text |Cite
|
Sign up to set email alerts
|

Lack of CHEK2 Gene Mutations in Differentiated Thyroid Carcinoma Patients using High Resolution Melting Analysis

Abstract: Recently, mutations in the genes involved in cell cycle control, including CHEK2, are being considered as etiological factors in different kinds of cancers. The CHEK2 protein plays an important role in protecting damaged DNA from entering mitosis. In this study the potential effects of two common mutations IVS2+1G"A and Ile157Thr of CHEK2 gene in differentiated thyroid carcinoma (DTC) were evaluated. A total of 100 patients admitted to the Research Institute for Nuclear Medicine were diagnosed with DTC based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In this study, the incidence of CHEK2 mutations was 65/427 (15.2%), which is comparable to our previous findings [17]. By contrast, other studies by Fayaz et al and Alzahrani et al in Middle Eastern populations identified no CHEK2 mutations, perhaps due to ethnic or geographical differences [18,19]. In a study reported by Wójcicka et al in 2014, the variant I157T was identified as a risk factor for PTC (OR = 2.2, P = 2.37e-10) [56], using data from a large group of patients with PTC (n = 1781) and healthy control subjects (n = 2081).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, the incidence of CHEK2 mutations was 65/427 (15.2%), which is comparable to our previous findings [17]. By contrast, other studies by Fayaz et al and Alzahrani et al in Middle Eastern populations identified no CHEK2 mutations, perhaps due to ethnic or geographical differences [18,19]. In a study reported by Wójcicka et al in 2014, the variant I157T was identified as a risk factor for PTC (OR = 2.2, P = 2.37e-10) [56], using data from a large group of patients with PTC (n = 1781) and healthy control subjects (n = 2081).…”
Section: Discussionsupporting
confidence: 86%
“…CHEK2 mutations, which occur in various sporadic cancers, predispose individuals to several types of hereditary malignancy, including thyroid cancer [13,14,15]. According to The Cancer Genome Atlas [16], mutations in CHEK2 are present in only 1.2% of patients with PTC, and are not mutually exclusive with other mutations involved in the MAPK signaling pathway, although frequencies of CHEK2 mutations ranging from 0% to 15.6% have been reported in patients with PTC [13,16,17,18,19]. Moreover, defects in DNA repair may be one mechanism underlying the features of more aggressive PTC [16].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we found that the overall frequency of mutations in the CHEK2 gene in PTC patients was 15.5%, which is in agreement with previous study results [ 23 , 43 ]. However, the TCGA 2014 study conducted in a North American population found that the CHEK2 mutation was present in only 1.2% of PTC patients, whereas Alzahrani et al and Fayaz et al found no mutations in the CHEK2 gene in Middle Eastern populations [ 38 , 41 , 42 ]. This may be related to geographic or ethnic differences, or (albeit rather less likely) to different techniques used to detect mutant alleles.…”
Section: Discussionmentioning
confidence: 99%
“…If DNA damage is not repaired, apoptosis is activated to remove the damaged cell from the body. Mutations in genes encoding proteins involved in DNA repair processes affect their stability or activity, which may contribute to neoplastic changes in cells [ 37 , 38 ]. Loss of kinase function due to mutations in the CHEK2 gene is associated with an increased risk of developing a variety of sporadic and hereditary malignancies, including PTC [ 32 , 37 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation